Qualitative properties of solutions of one class of evolutionary systems - Shevchenko, A. I.; Minenko, A. S. (Reports of the National Academy of Sciences of Ukraine, 2015)
The nonlinear nonstationary systems used as approximations to the well-known Bean model in the theory of type-II superconductivity in the 3D case are studied. An analogous system with convection term playing the role of damping is considered as well. These systems are closely related to the system of equations for a porous medium. The finiteness of the carrier of a solution of the Cauchy problem for nonlinear nonstationary systems in the 3D case is established.